Vector-independent transmembrane transport of oligodeoxyribonucleotides involves p38 mitogen activated protein kinase phosphorylation. Issue 1 (December 2017) - Peng, Minyuan; Li, Yanming; Zhang, Jian; Wu, Yong; Yang, Xiaoyang; Lei, Ye; Ye, Mao; Liu, Jing; Han, Xu; Kuang, Yijin; Zhao, Xielan; Chen, Fangping
Abstract The main roles of equilibrative nucleoside transporters (ENTs) and concentrative nucleoside transporters (CNTs) are to transfer single nucleosides and analogues for the nucleic acid salvage pathway. Oligodeoxyribonucleotides (ODNs) can be transported into the cytoplasm or nucleus of cells under certain conditions. Among ODNs composed of a single type of nucleotide, the transport efficiency differs with the length and nucleotide composition of the ODNs and varies in different types of leukaemia cells; among the 5 tested random sequence ODNs and 3 aptamers with varying sequences, the data showed that some sequences were associated with significantly higher transport efficiency than others. The transport of ODNs was sodium, energy, and pH-independent, membrane protein-dependent, substrate nonspecific for ODNs and 4-nitrobenzylthioinosine (NBMPR)-insensitive, but it showed a low sensitivity to dipyridamole (IC50 = 35.44 µmol/L), distinguishing it from ENT1-4 and CNTs. The delivery efficiency of ODNs was superior to that of Lipofection and Nucleofection, demonstrating its potential applications in research or therapeutics. Moreover, this process was associated with p38 mitogen activated protein kinase (p38MAPK) instead of c-Jun N-terminal kinase (JNK) signalling pathways. We have denoted ODN transmembrane transport as equilibrative nucleic acid transport (ENAT). Overall, these findings indicate a new approach and mechanism for transmembrane transport of ODNs.